Performance analysis of languages working on Java Virtual Machine based on Java, Scala and Kotlin - Buszewicz, Katarzyna (Journal of Computer Sciences Institute, 2020)
This article presents the results of a literature study related to the construction and operation of Java Virtual Machine, as well as performance tests of selected languages using the aforementioned runtime environment on the example of Java, Scala and Kotlin. Performance testing was carried out using two applications built using the Apache Maven archetype with the built-in Java Microbenchmark Harness library.